PREDICTION OF HEATING TIME OF CLEAR SINGLE-LAYER TPU ORTHODONTIC ALIGNER TRAYS: AN IN VITRO STUDY (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the variation in heating time of single-layer thermoplastic polyurethane (TPU) sheets and to develop a predictive model describing the trend of heating time across consecutive thermoforming cycles.Methods: An in vitro study was conducted on 140 single-layer TPU sheets (Maxflex, 0.76 mm thickness) thermoformed using a Drufomat Scan machine (Dreve, Germany). 7 independent experimental sessions were performed, each consisting of 20 consecutive thermoforming cycles starting from a cold-start condition. Heating time was recorded when the sheet reached a standard sagging depth of 16 mm, measured using a laser monitoring system. Data were analyzed using a non-linear mixed-effects model, Student’s t-test, and Bonferroni multiple comparisons.Results: The heating time decreased from 113.86 ± 1.57 seconds in the first thermoforming cycle to approximately 69-70 seconds from the 12th cycle onward. Statistically significant differences were observed between cycles 1-11 (p < 0.05), after which the system reached a thermal steady state. The observed heating time was significantly longer than the manufacturer’s recommended 30 seconds (p < 0.001). The non-linear mixed-effects model demonstrated an exponential decay pattern with an asymptotic value of 66.35 seconds (R² = 0.97).Conclusions: The heating time of single-layer TPU depends on the number of thermoforming cycles and stabilizes after approximately the 12th cycle. The actual heating time was substantially longer than the manufacturer’s recommendation, indicating the need for calibration and standardization of heating parameters under real operating conditions to ensure the accuracy of clear orthodontic aligners.
Keywords: Clear orthodontic aligners, thermoforming, heating time, single-layer TPU, nonlinear mixed-effects model.